Penerapan teknologi rocket stove sebagai solusi pengelolaan sampah ramah lingkungan di Desa Mergowati, Kecamatan Kedu, Kabupaten Temanggung - Christofel Natanael Butar Butar; Fahrezi Abdan Al Ghifary; Muhammad Wijdan Nabil; Regeng Dwi Raharjo; Salsabilla Siti Mustafiah; Adysha Citra Maharani; Norra Sefia; Evi Juliani Ayu Pratiwi; Riska Deviana; Handayani Agustina; Asih Marlina; Mohammad Aulia Rachman; Wahyanto Wahyanto (Nur Science Institute, 2025)
Waste management remains a major issue in Indonesia, particularly in rural areas, where open burning is common. This practice contributes to environmental pollution and increases the risk of community health problems. The UNNES GIAT 12 program implemented rocket stove technology in Mergowati Village, Kedu Subdistrict, Temanggung Regency, as an environmentally friendly and sustainable approach to organic waste management. This research-based community service initiative evaluated the effectiveness of rocket stoves in reducing organic waste volume, lowering potential environmental and health impacts, and promoting their use as a community-based alternative energy source. The program applied a Participatory Action Research (PAR) approach, involving residents and village officials in needs identification, stove construction, operational training, and evaluation. Results showed that the rocket stove reached an average temperature of 615°C within 13 minutes, reduced waste volume by up to 90%, and significantly decreased smoke emissions compared to open burning. The remaining ash can be reused as organic fertilizer, adding value to local agriculture. Most residents perceived the technology as easy to operate, safer, and feasible for sustained use.